Laparoscopic Diagnosis and Treatment of Gossypiboma Postconventional Ovariohysterectomy in a Bitch. (20th August 2021) - Brun, Maurício Veloso; Basso, Paula Cristina; de Oliveira, Marília Teresa; Dalmolin, Fabíola; Pinto-Filho, Saulo Tadeu Lemos; Hartmann, Helen Fialho; Abati, Stephanie Lanzarini; Machado-Silva, Marco Augusto; Müller, Daniel Curvello de Mendonça; Sanchez-Margallo, Francisco Miguel
Abstract : Introduction . Gossypiboma is a rare surgical complication in small animals. The authors reported the laparoscopic diagnosis and treatment of an abdominal gossypiboma and chronic draining fistula postopen ovariohysterectomy (OVH) unresponsive to medical treatment in a bitch. Case Presentation . The patient had undergone OVH and exploratory laparotomy in other veterinary practice 3 years previously. The animal, presenting a chronic fistula, was then referred to UFSM Veterinary Hospital. Ultrasonographic examination revealed a structure compatible with a granuloma. For the laparoscopic procedure, a 3-port (two at 11 mm; one at 6 mm) access was used. Adhesiolysis and mass removal were performed by blunt dissection and bipolar electrocoagulation. The fistula was treated by mobilising the omentum through it. There were no intra- or postoperative complications. The chronic wound showed first intention healing. The mass was composed of fibrous tissues surrounding one surgical gauze. Discussion and Conclusion . The removal of a retained surgical gauze in the abdomen by laparoscopy has already been described in medicine. However, a laparoscopic approach for treating a fistulous draining tract due to a gossypiboma has not been previously reported in dogs. Laparoscopic exploration of the fistula allowed the use of a pedicled omental flap through infected sites to control chronic infection. Laparoscopic surgery can be used to identify and treat abdominal gossypiboma in dogs, including those with chronic abdominal sinus.